Nutrional Impact on Associated Features in Children with Cerebral Palsy - Saleha Komal, Wajiha Shahid, Kiran Afzal, Hafiz Muhammad Manan Haider, Farwa Abid, Hira Khalid, Suhail Karim, Hafsah Khattak (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cerebral palsy is Non-Progressive developmental disability disorder in children. CP used for a broad term umbrella term for various neurological conditions that effects movements and posture because of damage in developing brain in early stages. There are topographically classifications which are based on effective part of body due to brain damage in CP. It includes Monoplegia, dieplagia, hemiplegia, paraplegia, Trapaga, quadriplegia. Types of CP with brain lesion include Spastic CP, Ataxic CP, Athletic CP, Dystonic and Mixed cerebral palsy. Objectives: To evaluate the effect of nutritional status on associated symptoms in children with cerebral palsy. Material and Methodology: A Cross Sectional Survey was conducted to evaluate the nutritional status and associated symptoms in cerebral palsy children. The sample was collected from PIMS, NIRM and HFH hospital, after taking Approval from REC and the setting. A total of 257 CP children with ages between 2 to 12 years and fulfilling inclusion and exclusion criteria were included in the study. Children were assessed using CPQL, CHQ and Nutritional assessment chart. Data collection tools/instruments structured questioner guide was used to collect data. From these questionnaires, data was collected about cerebral palsy children. Statistical Analysis: Demographic details are measured through calculating the percentages. Data will be analysed through SPSS version 21 Results: Out of 257 children 195 were having fiber in diet, 62 were not reported to have any fiber diet, 209 were having protein in diet and 48 were not reported to have any protein diet, 232 were having carbohydrate in diet and 25 were not reported to have any carbohydrate diet. Conclusion: Most of the children were suffering from GIT problems with most of the cases reporting of constipation and alternating Diarrhoea. Children who were at low level of GMFCS were having CNS symptoms i.e. balance problem and seizures and children with low BMI were showing CVS, respiratory and renal symptoms. Keywords: Ataxia, CP cerebral palsy, Nutritional Status, Ataxia, Spastic